Peculiarities of Operator Shooting of Television Programs in Interiors - Баталіна Христина; Дмитро Шатило (Вісник Київського національного університету культури і мистецтв. Серія: Аудіовізуальне мистецтво і виробництво)
The purpose of the research is to examine the distinctive characteristics of the process of filming television programmes in the interior and their impact on visual art and audience perception. In order to gain insight into the crucial elements that shape the quality of the resulting television content, this study will investigate the use of light, shot composition and mise-en-scène. Furthermore, this study will examine the factors that influence the choice of interior locations for filming, including financial constraints, availability of resources and equipment, and the specifics of the programme content itself. Research methodology. The following methods were employed: a theoretical approach was used to analyse existing scientific literature and publications within the field of media studies. This enabled the concepts that reveal the essence and functionality of camera crews filming television programmes to be systematised and organised. The empirical method was employed to conduct practical research, collect data and conduct interviews with experts. The resulting data was then processed and analysed to study the impact of these programmes on the audience and their perception. The system-analytical method was used to analyse the relationships between various elements of authoring television programmes and their effect on viewers. The scientific novelty. The article presents a novel scientific contribution to the field. The study emphasises the necessity of comprehending and considering these elements for professionals producing television programmes and visual arts. It also identifies potential avenues for enhancing the quality of television content and optimising its impact on the audience, ultimately determining the programme's success. Conclusions. The study highlights the necessity for further advancement and enhancement of knowledge in the domain of television programme production within interior settings. Examining the author’s programmes illustrates the significance of lighting and shot composition for creating premium television content. A comprehensive comprehension of the constraints and prospects of interior filming is a pivotal element in enhancing its quality and impact on viewers.